2020
DOI: 10.1007/s00420-020-01544-3
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain among offshore wind industry workers: a cross-sectional study

Abstract: Objective To assess whether there are differences in musculoskeletal pain among different types of occupations offshore and their relationship to ergonomic demands. Methods We conducted a web-based cross-sectional survey among workers from offshore wind energy companies operating within the German exclusive economic zone. We selected workers with regular offshore commitments and at least 28 days spent offshore in the past year (n = 268). Musculoskeletal pain was assessed using the Subjective Health Complaints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…seem to pose risks for LBP [ 18 , 19 ]. The most commonly reported biomechanical risk factors with at least reasonable evidence for causing LBP include excessive repetition and awkward postures [ 20 , 21 ]. Several recent epidemiological studies have shown that psychosocial factors (e.g., job demand, job control, and social support) may increase the risk of developing LBP [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…seem to pose risks for LBP [ 18 , 19 ]. The most commonly reported biomechanical risk factors with at least reasonable evidence for causing LBP include excessive repetition and awkward postures [ 20 , 21 ]. Several recent epidemiological studies have shown that psychosocial factors (e.g., job demand, job control, and social support) may increase the risk of developing LBP [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the European Union, 32% of workers have reported that their work requires carrying and moving heavy loads at least one quarter of their workday, while in the US this statistic goes over 40% [1]. Carrying or moving heavy loads has been associated with several musculoskeletal disorders [4] including leg pain [5], hip and knee disorders [6], back pain [7,8], chronic low back pain [9], lumbar spine disorders [10,11], and neck and upper limb pain [7,12]. The Bureau of Labor Statistics (BLS) reports that musculoskeletal injuries resulting in days away from work affect 38% of laborer and freight, stock and material movers, and 52% of nursing assistant [13].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include remote work conditions, seasonal work, irregular work/leave schedules, long working shifts, and uncertainty in tasks dependent on weather conditions [ 4 – 9 ]. The prevalence of musculoskeletal disorders among WTs has further been associated with the physical work demands offshore, specifically in terms of turbine type on location (size), the duration of work in awkward postures, and manual handling activities [ 6 , 10 ]. Objectively assessed physical work demands among WTs support the notion of substantial physical requirements.…”
Section: Introductionmentioning
confidence: 99%